Dynamische Fähigkeiten der Exportdienstleister im Obst- und Gemüsesegment: Ansatzpunkte zur Überwindung von internen Exportbarrieren; Dynamic Capabilities of Export Service Providers in the Fruit and Vegetable Sector: Approaches to Overcome Internal Export Barriers - Haydee Calderoń Garcia; Diana Kolbe (German Journal of Agricultural Economics (GJAE), 2017)
In dieser Studie wird untersucht. welche Auswirkungen dynamische Fähigkeiten beim Export von frischem Obst und Gemüse im Bereich der kleinen und mittelgroßen Unternehmen im Zwischenhandel haben können.Die Grundlage dieser explorativen, qualitativen Studie bilden Tiefeninterviews. Die Ergebnisse zeigen, dass dynamische Fähigkeiten wie das Beziehungsmanagement, die Verbraucherorientierung, die Transparenz und die Kommunikation entlang der Wertschöpfungskette sowie das Markenmanagement dazu beitragen können, einen Großteil der internen und strategischen Hindernisse zu überwinden und das Exportergebnis positiv zu beeinflussen. –SW: Distribution von Obst und Gemüse; Dynamische Fähigkeiten; Exportleistung; Exportdienstleister – – Intermediaries are the mainstay of fruit and vegetable commercialization in foreign markets. However, they face strategic problems that undermine their competitiveness and impede their international development. In order to compete in export markets, these mainly small and medium-sized enterprises require dynamic capabilities which are not possessed by all of them. Existing research has not fully researched dynamic capabilities which determine the success in the exportation of fresh fruit and vegetables. Based on seven in-depth interviews, our contribution in this work is to determine what specific dynamic capabilities of the fruit and vegetable distributing companies contribute to an improvement in the export performance. The results of the conducted explorative and qualitative study show that four dynamic capabilities, the relationship management, the consumer orientation, the transparency and the communication along the value chain and brand management can help to solve most of the internal barriers and strategies and as a consequence influence positively in the export results.
Keywords: 330